Peningkatan Efisiensi Picking Dengan Menggunakan Order Batching Statis – Earliest Due Date - Chandra, Agung (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2017)
Order Picking activity has about 55% of warehouse operational cost. Because of that, a company XYZ, management views that warehouse activities which employs human energy need to be improved and be efficient. One of the strategies is to do order picking simultaneously for some customer orders, this way is common called Order Batching. The type of order batching is static and based on Earliest Due Date. The result of order batching implementation has an impact on reduction of travel distance about 31.8%.